Wideband Tunable Modified Split Ring Resonator Structure Using Liquid Metal and 3-D Printing - Rafi, Md Abdur; Wiltshire, Benjamin D.; Zarifi, Mohammad H. (IEEE microwave and wireless components letters, 2020)
Microwave split ring resonators (SRRs) are limited in modern designs to give a fixed resonant response based on their dimensions and material makeup. By designing an adjustable liquid metal component integrated in a highly coupled modified SRR, a frequency-tunable resonator structure was developed. The liquid metal integrated resonators were simulated to show that by varying the amount of liquid metal introduced to the system, the resonant frequency was continuously adjusted from 3.4 to 2.3 GHz, with a consistent resonant amplitude and quality factor of −22 dB and 75, respectively. The frequency-configurable sensor was fabricated with simple 3-D printing methods and inexpensive materials to control the liquid metal, resulting in a compact device with frequency tunability from 3.4 to 2.35 GHz. The fabricated resonator sensor had a resonant amplitude and quality factor of −24 dB and 70, respectively - with less than 10% variation along the entire frequency tuning process. Experimental analysis of the sensor showed continuous variation as the volume of liquid metal was increased within the straight channel, with a consistent resonant frequency sensitivity to liquid metal of 375 MHz/cm. The device enables measurement of a microwave frequency spectrum with user-desired resolution.